Sexual risk behaviours and their correlates among gay and non-gay identified men who have sex with men and women in Chengdu and Guangzhou, China. (October 2013) - Song, Dandan; Zhang, Hongbo; Wang, Jun; Han, Delin; Dai, Liping; Liu, Qi; Yu, Fei; Operario, Don; She, Min; Zaller, Nickolas
To better understand the behavioural characteristics and the factors associated with high risky behaviours among men who have sex with men and women (MSMW) with different orientation, we analyzed data from a cross-sectional survey of 600 MSMW in two large cities in China. Participants completed a questionnaire and underwent serological testing. Overall, human immunodeficiency virus (HIV) prevalence was 26%. In multivariable analysis of risk factors for unprotected anal intercourse in the past six months, factors associated with unprotected vaginal intercourse (UVI) were as follows: gay-identified orientation, having anal sex with a boyfriend, having multiple male partners, and never or sometimes using a condom for vaginal intercourse. In multivariate analyses of risk factors for UVI in the past 12 months, factors associated with UVI were as follows: non-gay-identified MSMW, having multiple male partners, having multiple female partners, and never or sometimes using a condom for anal intercourse. This study revealed a high prevalence of HIV and risky sexual behaviours.